IoT-Based Real-Time Monitoring System for Epidemic Diseases Patients: Design and Evaluation - Al-Mutairi, Abdullah W.; Al-Aubidy, Kasim M.; Al-Halaiqa, Fadwa N. (International Journal of Online and Biomedical Engineering (iJOE), 2021)
Epidemic diseases patients need constant monitoring of their health, whether in the hospital or at home, and this requires great costs. The employment of information and communication technologies and artificial intelligence concepts helps reduce these costs. This paper introduces a real-time monitoring system for monitoring pneumonia patients that will allow doctors to monitor the health of their patients remotely through smartphones or internet-connected devices. To verify the proper functioning of this system, a real-time monitoring device was developed. A secure mechanism is designed to establish a wireless connection to the monitoring unit.